Altruism and prosocial behavior in groups - Thye, Shane R.; Lawler, Edward J. (Emerald, 2009)
In this volume scholars from a variety of disciplines address a range of phenomena related to the general question of when people behave in an altruistic fashion. The specific topics addressed in this volume include how empathy induced altruism can actually be a threat to the some larger collective good, the role of egoism in the production and maintenance of social order, the basis of cooperation in social dilemmas, an evolutionary account of sex differences in the propensity to cooperate, a theoretical analysis of when individuals experience gratitude versus indebtedness in response to receiving help, a new status-driven theory of large scale collective action, a cross-national analysis of institutional versus generalized trust in societies, and how individuals develop expectations for the sanctioning of particular kinds of behaviors. Overall, the volume includes papers that reflect a wide range of theoretical approaches to altruism and prosocial behavior in groups from sociologists and psychologists who work in the general area of group processes.
Addresses a range of phenomena related to the general question of when people behave in an altruistic fashion. This book contains topics that include how empathy induced altruism can actually be a threat to the some larger collective good, and the role of egoism in the production and maintenance of social order.
Keywords: Social Science -- Sociology -- General.; Social groups.; Social, group or collective psychology.; Altruism.; elektronické knihy; electronic books